Technology transfer model for the Klang valley mass rapid transit development project - Hamdan, Abdul Rahman (2021)
Realising the strategic leverage that large-scale public procurement has on local technology development, several countries introduced a Technology Transfer (TT) programme into their public procurement as part of capability-building. Recognising this leverage, the government of Malaysia has also introduced this Technology Transfer programme into some government strategic procurements to develop local industries. Malaysia still depends heavily on foreign technology in certain sectors and this over-reliance is due to the ineffectiveness of the TT model currently being implemented. Arguably, effective implementation of TT by the government would help Malaysia to reduce this dependency. However, there is a lack of studies measuring the effectiveness of TT in Malaysia’s public mega-projects. This study provides an analysis of a case study involving the TT model used in a public rail infrastructure project in Malaysia. It aims to identify factors impacting the current effectiveness of the technology transfer process in the nation’s mega infrastructure project and propose a framework. The study was conducted using a mixed-method analysis of qualitative and quantitative data. The Klang Valley Mass Rapid Transit (KVMRT) project was selected as a suitable case study due to the massive amounts of capital and technology needed for its completion. The final output of the study is a four-stage TT model for the KVMRT project. The first stage is a literature review in which TT models from several studies were reviewed. Based on this review and comparison analysis, a conceptual KVMRT TT model was developed. To further investigate the key factors of the TT process in the project, two stages of study: primary study 1 and primary study 2 were conducted. Primary study 1 was conducted qualitatively to test and evaluate the conceptual model developed during the early stage with the identified key experts. Primary study 2 was conducted quantitatively using factor analysis and Structural Equation Modelling (SEM) to test and evaluate further the findings from primary study 1. A total of 202 respondents were selected from personnel who were directly involved in the KVMRT project and TT programme to participate in a survey. The fourth stage was the model validation stage, where a focus group and case studies are used to validate the findings from the primary study 2. Based on these findings and the validation exercise, a final KVMRT-TT model was developed. Six main factors that are highly influential were identified in determining the effective and successful outcome of the TT programme in the KVMRT project, namely: “Technology Transfer Planning”, “Transfer Environment”, “Learning Environment”, “Technology Provider’s Characteristics”, “Recipient’s Characteristics” and “Technology Transfer Outcome”. Among these factors, the “Learning Environment” was found to be the strongest factor influencing the TT outcome. This study made several recommendations to improve the TT process which include: (1) Improvement of current government policy on Technology Transfer, (2) Focus attention on innovations as one of the main criteria for a TT outcome, (3) Digitalization of the TT Process, (4) Proper measurement and evaluation of TT outcomes, and (5) Establishment of a Technology Transfer Office (TTO) in a government strategic procurement project.